Influence of adipose-derived mesenchymal stromal cells on osteosarcoma minimal residual disease - Aanstoos-Ewen, Megan, author; Ehrhart, Nicole, advisor; Kipper, Matthew, committee member; Dow, Steven, committee member; Custis, James, committee member (Colorado State University. Libraries, 2015)
Introduction: Mesenchymal stromal cells (MSCs) have been shown to improve bone integration and healing in several preclinical studies and have therapeutic potential in limb salvage following massive bone loss due to tumor resection. However, MSCs have also been shown to promote primary and pulmonary metastatic tumor growth when injected in the presence of gross tumor or when co-injected with tumor cells in rodent models. While these results raise concerns about the safety of using MSCs in sarcoma patients, MSCs are unlikely to be utilized in a clinical setting when gross tumor is present. The objective of this dissertation project was to develop murine models of minimal residual osteosarcoma following primary tumor removal then to utilize these models to determine whether the administration of adipose-derived MSCs with or without chemotherapy treatment in a minimal residual disease setting would promote either pulmonary metastatic osteosarcoma progression or local disease recurrence. We hypothesized that surgical site or intravenous administration of MSCs will influence either osteosarcoma pulmonary metastatic burden or local disease recurrence in a minimal residual disease setting. Materials & Methods: Two syngeneic, orthotopic models of luciferase-expressing osteosarcoma were developed. In the first model, tumor-bearing mice underwent a coxofemoral amputation and were followed to assess development of pulmonary metastases. In the second model, a femorotibial amputation was performed in order to develop a model of consistent local tumor recurrence. In this model, all gross tumor was removed, however, microscopic tumor remained at the surgical margin. In this dissertation project, three principle projects were completed to test our hypothesis. The first project explored the use of MSCs delivered either to the surgical site or intravenously to ascertain their influence on pulmonary disease burden. A follow-on pilot explored concurrent MSC and chemotherapy treatment on development of pulmonary disease. The second project evaluated the use of MSCs delivered either to the surgical site or intravenously on local recurrence of osteosarcoma at the surgical site. Gross recurrent tumor size was measured for comparison between treatment groups. The third project examined the use of cisplatin and MSCs on survival of mice following removal of primary osteosarcoma. Data were expressed in mean +/- SD or median with 95% CI. ANOVA test, Kruskal-Wallis test, Fisher’s Exact test, Welch’s test, t-test, and Mann Whitney test were used for statistical analysis. Significance was set at p<0.05. Results: Mice treated with intravenous MSCs had a faster time to first pulmonary metastatic disease detection than mice treated with MSCs injected into the surgical site or control mice (no MSCs) (p=0.022). No treatment effect was seen between groups with respect to time to tumor recurrence or size of recurrent tumor in the second study. Survival curves were significantly different when comparing cisplatin, cisplatin and MSC treatment, MSC alone treatment and untreated mice (p<0.001) as well as in pairwise comparisons. Mice treated with MSCs had a 73% chance of earlier death than untreated controls. Discussion/Conclusion: Intravenous administration of MSCs in a minimal residual osteosarcoma environment resulted in a faster time to first detection of pulmonary disease and in a higher chance of earlier death compared to untreated mice. However, administration of MSCs locally in a surgical site following sarcoma excision appears to be safe, even in the setting of known residual microscopic disease. Further, the use of cisplatin treatment appeared to ameliorate the effects of intravenous MSCs on survival. Based on these results, further study is warranted to evaluate the influence of intravenously administered MSCs on minimal residual pulmonary metastatic disease.
Keywords: mesenchymal stromal cell; osteosarcoma; murine; mesenchymal stem cell